The Effect of Plastiment-VZ on the Compressive Strength and Flexural Strength of Lightwieght Concrete Using Aluminium Powder - Yusuf, Khairullah; Siregar, Aida Rahmayani; Senin, Syahrul Fithry (Department of Information Technology, Universitas Malikussaleh, Aceh Utara, Indonesia, 2022)
One of the approaches to producing lightweight concrete is by adding the aluminum powder to the cement mixture to create air bubbles in the concrete as such enabling pores to appear in the concrete. Aluminum powder can reduce the weight of lightweight concrete despite its tendency to reduce compressive strength. The compressive strength of concrete can be increased by certain methods, one of which is by the addition of Plastiment-VZ admixture. This study aims to investigate the effect of the use of Plastiment-VZ admixture on the compressive strength and flexural strength of lightweight concrete. The normal concrete compressive strength is designed to the range of 0.7 MPa – 5.0 MPa. The concrete testing specimens were in the form of a cube of 15 cm x 15 cm x 15 cm for the compressive test and beams with dimensions of 15 cm x 15 cm x 60 cm for the flexural test. The test results of the compressive strength obtained for normally aerated concrete (0% of Plastiment-VZ) is 6.31 MPa; and for the variation of 0.2% is 6.52 MPa, for 0.4% is 6.8 MPa, and for 0.6% is 8.04 MPa. The highest increase in strength occurred at 0.6% variation, which is 27.46% above normally aerated concrete. The degrees of flexural strength of the concrete produced from each variation of 0%; Based on the findings, it can be concluded that Plastiment-VZ has a significant effect on increasing the compressive strength and flexural strength of lightweight concrete. The more quantity of Plastiment-VZ is used, the higher the compressive strength and flexural strength are produced; even though, the optimum level for the use of Plastiment-VZ for aerated concrete has not been found.